Thermodynamic Study of Complex Formation Between Cu(II) and 4-Amino-6-methyl-1,2,4-triazin-3-thione-5-one in Binary Ethanol/Water Mixtures using Conductometric Method - NEZHADALI, AZIZOLLAH; HAKIMI, MOHAMMAD; NAEMI, ASGHAR (Asian Journal of Chemistry, 2010)
The stability constant, Kf, for the complexation of copper(II) with 4-amino-6-methyl-1,2,4-triazin-3-thione-5-one (AMTTO) in 0, 20, 40, 60 and 80 (v/v) % ethanol-water mixtures were determined conductometrically at different tempratures. The stability constants of resulting 1:1 complexes were become larger by increasing of temprature and ethanol per cent. Stability constants of complexes vary inversely with dielectric constant of solvents. The enthalpy and entropy of complexation were determined from the temprature dependence of the formation constant. In all cases, the complexation were found to be enthalpy unstablized but entropy stablized. ΔGº of the studied complexes were evaluated at 25 ºC using thermodynamic relations, the negative values of ΔGº means that the complexation process is spontaneously.